2019
DOI: 10.1186/s40494-019-0245-2
|View full text |Cite
|
Sign up to set email alerts
|

Acid solution decreases the compressional wave velocity of sandstone from the Yungang Grottoes, Datong, China

Abstract: To understand the effects of an acidic environment on the internal structure of sandstone from the Yungang Grottoes, Datong, China, the physicochemical properties of fresh and weathered sandstone samples and their compressional wave (P-wave) velocities in response to different concentrations of H 2 SO 4 and HNO 3 solution were investigated. X-ray diffraction (XRD) and a scanning electron microscope equipped with energy dispersive X-ray spectrometer (SEM-EDX) were used to determine grain morphology and chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…China has a long history over 2500 years and has a great many stone historical relics across the whole country [ 4 , 5 , 6 , 7 , 8 , 9 ]. Shanxi province located in the northwest part of China is regarded as the cradle of Chinese civilization and is famous for its cultural relics, especially the stone relics e.g., Yungang Grottoes [ 10 ]. However, these stone heritage relics currently experience severe weathering and aging due to increasing air and water pollution (SO 2 , SO 3 , NO x etc.)…”
Section: Introductionmentioning
confidence: 99%
“…China has a long history over 2500 years and has a great many stone historical relics across the whole country [ 4 , 5 , 6 , 7 , 8 , 9 ]. Shanxi province located in the northwest part of China is regarded as the cradle of Chinese civilization and is famous for its cultural relics, especially the stone relics e.g., Yungang Grottoes [ 10 ]. However, these stone heritage relics currently experience severe weathering and aging due to increasing air and water pollution (SO 2 , SO 3 , NO x etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The presence of calcite cement in sandstone contributes to their susceptibility to acid attack [66] and has been related to the development of contour scaling under salt weathering [56]. Tuffs with predominance of glassy groundmass and pumice clasts presented higher susceptibility to salt weathering [67].…”
Section: Textural and Structural Featuresmentioning
confidence: 99%
“…Previous studies indicated that water is one of the main causes of weathering to the grottoes and the phenomena such as swelling, disintegration and softening occurred after the water penetrated and interacted with the rock, resulting in the reduction of stability. The various forms of occurrence and special action of slight seepage produced a cyclical effect to the Grotto rock mass, and turned to be a dominant factor, accelerating the deterioration and weathering destruction of rock mass [7][8][9][10][11]. The existence of fracture network usually functions as an underground water flow path, thus posing a serious threat to safety of grotto relics.…”
Section: Introductionmentioning
confidence: 99%